Membangun Koperasi Modern: Peningkatan Kapasitas Aparat Sipil Negara (ASN) di Lingkungan Dinas Koperasi dan Usaha Kecil (DISKUK) Provinsi Jawa Barat - Suseno, Gijanto Purbo (LPPM Universitas Koperasi Indonesia, 2025)
Training to increase ASN capacity in the Diskuk environment of West Java Province aims to increase ASN capacity regarding understanding the concepts and strategies of building modern cooperatives. Implemented properly hybrid at the Master of Management Study Program at the Indonesian Cooperative University on 24 to 26 July 2024, this training was attended by 85 participants. One of the main materials includes Concepts and Strategies for Building Modern Cooperatives, with teaching methods including lectures, discussions and case studies. The evaluation results showed a significant increase in participants' knowledge and skills, with 85% understand the concepts and strategies in building modern cooperatives. This training recommends the need for continuous training and support from various parties to ensure effective implementation of cooperative principles among ASN Diskuk in community empowerment activities. In addition, it is recommended that the West Java Province Diskuk expand the reach of training to other regions in order to increase the positive impact on cooperative development throughout the province.